CELLULAR SENESCENCE AS A THERAPEUTIC TARGET FOR GEROSCIENCE-GUIDED CLINICAL TRIALS. (8th November 2019) - Justice, Jamie N; Nambiar, Anoop M; Tchkonia, Tamar; LeBrasseur, Nathan K; Musi, Nicolas; Kritchevsky, Stephen B; Kirkland, James L
Abstract: The geroscience hypothesis holds that targeting fundamental mechanisms of aging has the potential to prevent or reduce severity of multiple age-related diseases. Cellular senescence is a key mechanism that may be driving disease in human aging, including Idiopathic pulmonary fibrosis (IPF), a progressive, ultimately fatal, senescence-associated disease. Importantly, cellular senescence may be targeted therapeutically. Senolytic agents are drugs that selectively induce senescent cell apoptosis by transiently disabling anti-apoptotic pathways. Selective ablation of senescent cells using the senolytic drug combination dasatinib plus quercetin (DQ) alleviates IPF-related dysfunction in bleomycin-administered IPF mouse model. We conducted the first-in-human trial of senolytics in IPF patients, and our data indicate that short-term, intermittent administration of DQ may alleviate physical dysfunction that accompanies IPF in human aging, including clinically-meaningfully improvements in mobility (p<0.05). This geroscience-guided clinical feasibility study supports evaluation of senolytics in larger randomized, controlled trials of cellular senescence-associated age-related diseases.